Penerapan Metode Kerja Kelompok pada Pembelajaran Matematika dalam Meningkatkan Prestasi Belajar Peserta Didik - Sisilia Mite Lestari Wanda; Gregorius We,u; Tebajak Henakin; Benedikta Boleng (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The objective of the research was to find out the application of group work method to improve students achievement in the material of the characters of multiplication at the fifth grade Inpres elementary school in Otobamba. It was a classroom action research (CAR). The techniques to collect the data were observation, interview, documentation, and test. The subject of the research was 16 students. The finding showed that the learning achievement of students in every cycle was improved. In cycle I the average passed score was 31,25 % or 5 students and the average failed score was 68,75 % or 11 students. In cycle II, there were 16 who pass or 100%. In conclusion, mathematics teaching by using group work method can improve students achievement. Keywords: Group Work Method, Achievement, Mathematic Teaching